The effect of pelvic radiation alone on lymphocyte subgroups. (July 2020) - Swanson, Gregory P.; Jhavar, Sameer G.; Hammonds, Kendall
Highlights: Radiation therapy alone has dramatic effects on lymphocyte subgroups. CD4+, CD8+ and CD56+ counts drop by >70%, CD 19+ by >90%. Three months post exposure, no subgroup has returned to baseline levels. All subgroups except CD 56+ (including CD19+) recovered modestly to about 40% of pre-treatment levels. CD56+ were more resistant and recovered to 64% of pretreatment levels. CD56+ cells recover more fully (to >60% of pretreatment levels). Abstract: There is a lack of information on the radiosensitivity of lymphocyte subgroups to radiation alone. CD4+ and CD8+ lymphocytes respond similarly. CD 19+ dropped most precipitously, but recovered to levels similar to the other subgroups by 3 months. NK cells decline more modestly and recover more fully by 3 months.